A Southeastern Baffin Thule House with Ruin Island Characteristics - Maxwell, Moreau S. (ARCTIC, 1981)
A prehistoric house depression excavated on the southeastern coast of Baffin Island near Lake Harbour belongs stylistically to an early phase of the Thule Period. However, features such as the rectangular shape, interior open-fire kitchens, and initial absence of a sleeping platform are more characteristic of the early High Arctic Ruin Island phase than of developed Thule. This, and additional evidence from Foxe Basin and Frobisher Bay, suggest that a segment of the earliest Thule migration may have split from the main body in Lancaster Sound and, travelling south through Fury and Helca Strait, reached Hudson Strait and the south coast of Baffin Island. This suggestion is in opposition to earlier interpretations of a slow penetration into the more southerly eastern part of the Canadian Archipelago from the northeastern High Arctic.